Anelasticity and Lateral Heterogeneities in Earth's Upper Mantle: Impact on Surface Displacements, Self‐Attraction and Loading, and Ocean Tide Dynamics. Issue 9 (12th September 2021) - Huang, Pingping; Sulzbach, Roman Lucas; Tanaka, Yoshiyuki; Klemann, Volker; Dobslaw, Henryk; Martinec, Zdeněk; Thomas, Maik
Abstract: Surface displacement and self‐attraction and loading ( SAL ) elevation induced by ocean tides are known to be affected by material properties of the solid Earth. Recent studies have shown that, in addition to elasticity, anelasticity considerably impacts surface displacements due to ocean tide loading (OTL). We employ consistent 3D seismic elastic and attenuation tomography models to construct 3D elastic and anelastic earth models, and derive corresponding averaged 1D elastic/anelastic models. We apply these models to systematically study the impact of anelasticity and lateral heterogeneity on M2 OTL displacements and SAL elevation. We find that neglecting lateral heterogeneities highly underestimates displacements and SAL elevation in mid‐ocean‐ridge regions and in some coastal areas of North and Central America. In comparison to PREM, 3D anelastic models can increase the predicted amplitudes of the vertical displacement and SAL elevation by up to 1.5 mm. The increased amplitudes reduce the discrepancy between GPS‐observed OTL displacements and their predictions based on PREM in places like Cornwall (England), Brittany (France), and the Ryukyu Islands (Japan). Applying our results to ocean tides, we discover that the impact on ocean tide dynamics exceeds the predicted SAL elevation correction with an RMS of about 1 mm, reaching an RMS of more than 5 mm in areas like North Atlantic or East Pacific. Due to the fact that such a value reaches the accuracy of modern data‐constrained tidal models, we regard the impact of anelastic shear relaxation as significant in tidal modeling. Plain Language Summary: How are the vertical displacement, sea level fluctuation with respect to the vertical displacement (hereafter SAL elevation) and ocean tide on Earth's surface affected by material properties of the Earth's interior? We study this problem using the ocean tide model TiME and two sets of 3‐Dimensional (3D) seismic elastic and attenuation models, one from the University of California, Berkeley and another from the École Normale Supérieure (ENS) de Lyon. Both the Berkeley and Lyon models confirm that strong lateral variations in elastic parameters and attenuation exist in places such as mid‐ocean‐ridge regions and some coastal areas of North and Central America. They cannot be neglected in modeling displacements and SAL elevation in these places. In addition, 1D attenuation has a strong impact on ocean tides in regions like North Atlantic or East Pacific. This impact is at the same level as the accuracy of modern data‐constrained tidal models. Key Points: Lateral heterogeneity in mantle elasticity derived from three‐dimensional seismic tomography models including attenuation Modeling of deformations and self‐attraction and loading using a gravitationally consistent formulation Feedback of lateral heterogeneity and mantle anelasticity to ocean dynamics due to deviations in self‐attraction and loading